Multidrug Resistant Mycobacterium tuberculosis Among Military and Civilian Personnel seen at a Tertiary Military Hospital, Manila, Philippines (2015–2018). Issue 7 (9th January 2020) - Velasco, John Mark; Gaurano, Noel; Valderama, Maria Theresa; Nogrado, Kathyleen; Diones, Paula Corazon; Lopez, Ma Nila; Liao, Cynthia; Chua, Domingo; Develos, Maribel; Fernandez, Stefan; Macareo, Louis; Swierczewski, Brett
Abstract: Introduction: About one third of the world population is estimated to be infected with Mycobacterium tuberculosis (MTB), and this proportion is expected to be higher in countries with a high tuberculosis (TB) burden. The Philippines is both a high tuberculosis burden and a high multidrug resistant tuberculosis (MDR-TB) burden country. Though TB has been extensively described in the civilian population, there is limited data on TB in the military population. The objectives are: (1) To determine MTB/MDR-TB prevalence among military and civilian patients in the Philippines presenting with clinically suspected TB in a tertiary military hospital and (2) To determine performance of direct sputum smear microscopy (DSSM) using Ziehl-Neelsen (ZN) staining compared to Xpert MTB/RIF real-time reverse transcriptase polymerase chain reaction. Materials and Methods: Sputum samples were obtained from patients, clinically suspected with TB, and/or with TB associated signs/symptoms. Sputum specimens were tested using DSSM with ZN staining and Xpert MTB/RIF assay (Cepheid, Sunnyvale, California) and patient demographic and clinical data were collected. Results: From March 2015 to December 2018, a total of 795 (173 military personnel [164 active duty and 9 retired]; 618 civilians; and 4 with no data on military/civilian status) patients with TB associated symptoms or clinically suspected with TB were tested. Overall, MTB prevalence was 81/795 (10%). MTB prevalence among active duty and retired military personnel were 27/164 (16%) and 4/9 (44%), respectively while MTB prevalence for civilian patients was 50/618 (8%) ( p value = 0.0003; OR = 2.48 [95% C.I. 1.5–4]). Among active and retired military personnel who tested positive for MTB, rifampin resistance was 4/27 (15%) and 1/4 (25%), respectively, while rifampin resistance for civilian patients was 9/50 (18%) ( p value = 1; OR = 0.88 [95% C.I. 0.26–2.90]). For active duty military personnel, average MTB prevalence (based on Xpert MTB/RIF) covering years 2015–2018 was 21% and ranged from 13% to 35%, while average rifampin resistance among MTB positive active duty military personnel was 15% and ranged from 0% to 25%. Overall sensitivity and specificity of DSSM compared to Xpert MTB/RIF were 70% and 96%, respectively. Positive and negative predictive values of DSSM to accurately categorize MTB in symptomatic cases (with Xpert MTB/RIF as "true positive" reference) were 74% and 95%, respectively. Performance of DSSM varied according to MTB load detected by Xpert MTB/RIF with increasing DSSM sensitivity observed as the MTB load detected by Xpert MTB/RIF increased ( p  = 0.02). Conclusion: This report describes high MTB and MDR-TB prevalence rates among symptomatic military patients with military personnel having higher odds of MTB infection compared to the civilian patients in the study. Since DSSM (ZN) sensitivity greatly varied depending on MTB load, the Xpert MTB/RIF should be used as a first-line diagnostic tool to identify MTB and detect rifampin resistance among presumptive TB cases instead of DSSM (ZN) microscopy.